Microstructures and Dielectric Properties Of pb (Al,Vl-,)Ohs Systems - Primus, Walter Charles (2005)
The microstructures and electrical properties of Pb(AlxV1-x)03*cse ramic have been investigated. The samples were prepared using solid-state technique and were sintered at 800 OC, 850 OC and 900 OC. Surface morphology studies show that small grains with submicron size - 0.25 pm coexist with the bigger grains in micron size. As the sintering temperature increased, the grains size increase and thus become more compact. From )(RD analysis, the sample structure obtained is an orthorhombic system with space group PMMA and unit cell volume is 469.595 A3. The dielectric constant, e' for sample PAV 71800, PAV 71850 and PAV 71900 increased as the sintering temperature increased where the values of E' for sample sintered at 900 O C is - 6000 at 10'~H z and - 90 at 1 kHz. However, the loss factor, E" for sample sintered at 900 O C is higher than that of other samples. The loss tangent, E"/E' for sample PAV 71800, PAV 71850 and PAV 71900 at 1 kHz are 0.1, 0.12 and 0.16 respectively. The PAV 0.9 shows the highest E' -4000 at Hz but the E" for this sample is also high. This is followed by sample PAV 0.7 and PAV 0.3. Between frequencies higher than 1 kHz, the magnitudes of the E' data dispersion (- 80) are similar for samples PAV 0.3, PAV 0.7 and PAV 0.9. At 1 0-2 Hz to 1 kHz, the dispersion of E' is strongly dependent on frequency. However, the E' dispersion is independent with frequency at 1 kHz to lo5 Hz. The mechanisms that are observed from all samples are quasi dc, dipolar and barrier layer. A peak observed at lo2 Hz is due to the ionic relaxation processes. The activation energy that is obtained from sample PAV 71800 is 0.416. It indicates that the electrons hopping are weak. An equivalent circuit model has been proposed to represent the mechanism observed. The conductivity, ,o is increased from 3.0x10-~to 8.0x10-~r nholm for sample PAV 71800 and PAV 71900 respectively. For other samples with different Al composition, o, increased from 1.0x10-~ to 1.0x10-~ mholm for sample PAV 0.3 and PAV 0.9 respectively. The o, curve exhibits two distinct regions where the low frequency region is weakly dependent on frequency due to free charge carriers while the high frequency region is strongly dependent with frequency due to bound charge carriers in this sample. The IS, is increased from to lo4 mholm for 50 O C and 290 "C respectively. The activation energy of sample PAV 71800 and PAV 0.1 is -0.65 eV and may be due to the ac conduction in terms of hopping transport of charge carrier in a narrow band of localization states as the Fermi level. In complex impedance plots, only one semicircle is observed at low frequency and does not started fiom the origin due to the high frequency resistance effect. For sample PAV 71800, the resistance obtained from the plot is 8 . 9 9 ~ 1 0oh~m /m and the value of the capacitance is 1.5x10-'~F . The capacitance value obtained is in the range of bulk ferroelectric mechanism. In direct current measurement, the curve obtained obeyed the Ohm's law and the activation energy increased from 0.85 eV to 1.15 eV was the sintering temperature increases from 800 O C to 900 O C and 0.71 eV to 1.62 eV when A1 compositions increase from PAV 0.1 to PAV 0.9.